Company disclosures concerning the resilience of cities from the Sustainable Development Goals (SDGs) perspective. (April 2020) - Acuti, Diletta; Bellucci, Marco; Manetti, Giacomo
Abstract: Although companies are decisive in contributing to urban resilience, unresolved questions remain about which practices they can implement. Considering that the concept of resilience is acknowledged both explicitly and implicitly in a range of Sustainable Development Goals (SDGs), this research aims to fill the existing gap between theoretical considerations about the role of companies in fostering urban resilience and the practices they implement and disclose. First, we build a theoretical framework based on strategic and instrumental components that can support the contribution of companies to urban resilience. Subsequently, we analyze 138 sustainability reports from organizations operating in Italy and Japan to identify how the SDGs, in particular those targets concerning environmental and social resilience, are implemented in their activities and communicated in their nonfinancial reports. Because greater attention to disclosures on the impacts of companies on resilience is a starting point for action towards achieving the SDGs, this study provides new insights into the contribution of companies to the resilience of cities, thus advancing the literature on the link between business and urban resilience. Highlights: Resilience is acknowledged both explicitly and implicitly in a range of SDG targets. New insights into the contribution of companies to the resilience of cities. Theoretical framework based on strategies and instruments for urban resilience. Content analysis of 138 GRI sustainability reports of Italian and Japanese companies. Biodiversity, prevention and governance as the main strategies addressed by companies.